Pengaruh Elemen Fraud Pentagon Terhadap Financial Statement Fraud dengan Komite Audit Sebagai Moderasi - Andi Octavianus Lauwrens; Harti Budi Yanti (Publikasi Indonesia, 2022)
This study aims to analyze the impact of the fraud factor of the pentagonal model on financial reporting fraud at companies in the fields of property, real estate and construction listed on the Stock Exchange. Indonesia in the period 2018-2020. The study focused on companies in the property, real estate and construction sectors that had a period of study. 2018-2020. The sample was selected on the basis of purposeful sampling to obtain 19 firms with 57 observational data. Data analysis was performed using panel data regression. The obtained results show that pressure, opportunity, rationalization and competence have a significant impact on the likelihood of fraud in the financial statements. While arrogance cannot have a significant impact. The audit committee has demonstrated its ability to control the effects of pressure, opportunity, reasonableness and capacity on the potential for fraud in the financial statements.